Optimization of the Dikyasa Satlantas Unit in Overcoming Traffic Violations Among Students in Pekanbaru Police Jurisdiction - Faisal Muhammad (Indonesian Journal of Police Studies, 2021)
The background of the problem in this study is the increase in the number of traffic violations in the last three years. From this figure, students are one of the groups that commit the most traffic violations. This must be taken seriously because students who are still underage must have obedience to existing regulations. In this case, the Police have the main task of fostering the community to increase community participation, public legal awareness, and the obedience of citizens to the law and statutory regulations. The purpose of this study is to describe the activities carried out by the Dikyasa Unit in order to tackle traffic violations among students in the Pekanbaru Police jurisdiction and also to describe the factors that affect the Dikyasa unit in tackling traffic violations among students in the Pekanbaru Police jurisdiction. . This study uses a qualitative approach, while the theories and concepts used to analyze this problem are Management Theory, Motivation theory, Competence theory, Optimization concept, Traffic Security and Trafficking concepts, and Traffic Violation Concepts from the Indonesian National Police Chief Implementation Instructions No.Pol: Juklak/5/ V/2003 dated May 29, 2003 concerning Guidelines for the Implementation of Public Education in the Traffic Sector. Data collection techniques that can be used are interviews, observation, and document studies. The results obtained in this study are the implementation of activities carried out by the Pekanbaru Police Satlantas Dikyasa unit is still not optimal, related to the budget and human resources that are still lacking, Traffic and Traffic Security in Pekanbaru City is also still far away because there are still many violations. The author suggests to the Pekanbaru Police Chief to increase the number of Dikyasa Unit personnel and to the Head of Traffic to implement a reward and punishment system for members as well as for the Principal and also the parents of the students to coordinate and cooperate with the Satlantas in supervising students. to comply with traffic regulations.